Solar assisted heat-pump dryer and water heater - Hawlader, Mohammad Nurul Alam; Chou, S K; Rahman, S M A; Lau, K W Eugene (Elsevier, 2003)
A solar-assisted heat-pump dryer and water heater has been designed, fabricated and tested. The performance of the system has been investigated under the meteorological conditions of Singapore. The system consists of a variable-speed reciprocating compressor, collector evaporator, storage tank, air-cooled condenser, auxiliary heater, blower, dryer, dehumidifier, and air collector. The drying system is designed in such a way that some of the components can be isolated depending on the weather conditions and usage pattern. The drying medium used is air and the drying chamber is configured to carry out batch drying of food grains. A simulation program is developed using Fortran language to evaluate the performance of the system and the influence of different variables. The performance indices considered to evaluate the performance of the system are: Solar Fraction (SF) and Coefficient of Performance (COP) with and without water heater. The values of COP, obtained from the simulation and experiment are 7.0, and 5.0, respectively, whereas the solar fraction (SF) values of 0.65 and 0.61 are obtained from simulation and experiment, respectively.